Pivot Table Analysis of Housing Conditions and Dampness Factors: Implications for Health and Well-being of Building Structure - Mujahid Faiyas Husain, Sonwane Dimpleben Prokashbai (Mathematical Statistician and Engineering Applications, 2023)
This research paper presents the findings of a survey conducted in Nashik, Maharashtra, aiming to assess housing conditions and indoor environmental factors and their implications for health and well-being. The survey collected feedback from 400 respondents and employed pivot table analysis to examine various aspects related to housing characteristics, maintenance history, structural integrity, indoor environmental factors, and their potential effects on occupants’ health. The results shed light on the current housing conditions and provide valuable insights for policymakers, practitioners, and individuals seeking to improve housing quality and create healthier indoor environments.